2017
DOI: 10.1080/09513590.2017.1290066
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2, CAPN10 polymorphisms are associated with gestational diabetes mellitus (GDM) risks: a meta-analysis

Abstract: Several polymorphisms have been identified in transcription factor 7-like 2 (TCF7L2), and calpain-10 (CAPN10) genes. Controversial conclusions for the genetic relationship between these polymorphisms and gestational diabetes mellitus (GDM) risks were obtained. Our study aims at assessing whether these polymorphisms are associated with GDM susceptibility via a meta-analysis. A total of 19 eligible case-control articles were obtained after databases searching. A significantly increased GDM risk was observed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Among the most significant genes whose expression is regulated by epistatic interactions, Capn10 is particularly interesting given its controversial association with T2D risk. It was the first T2D susceptibility gene identified in linkage studies (HORIKAWA et al 2000), with multiple subsequent GWAS or candidate gene studies having also identified an association between variants near CAPN10 and T2D risk and other diabetes-related phenotypes (BAIER et al 2000;EVANS et al 2001;OROZCO et al 2014;IBRAHIM et al 2015;CUI et al 2016;ZHAO et al 2016;BAYRAMCI et al 2017;HOU et al 2017;CASTRO-MARTINEZ et al 2018). However, many other studies failed to replicate these findings (HEGELE et al 2001;TSAI et al 2001;KHAN et al 2014;AL-SINANI et al 2015;PLENGVIDHYA et al 2015;ZHANG et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Among the most significant genes whose expression is regulated by epistatic interactions, Capn10 is particularly interesting given its controversial association with T2D risk. It was the first T2D susceptibility gene identified in linkage studies (HORIKAWA et al 2000), with multiple subsequent GWAS or candidate gene studies having also identified an association between variants near CAPN10 and T2D risk and other diabetes-related phenotypes (BAIER et al 2000;EVANS et al 2001;OROZCO et al 2014;IBRAHIM et al 2015;CUI et al 2016;ZHAO et al 2016;BAYRAMCI et al 2017;HOU et al 2017;CASTRO-MARTINEZ et al 2018). However, many other studies failed to replicate these findings (HEGELE et al 2001;TSAI et al 2001;KHAN et al 2014;AL-SINANI et al 2015;PLENGVIDHYA et al 2015;ZHANG et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The calpain 10 (CAPN10) gene has a role in the control of blood glucose concentrations and structural changes in the calpain 10 protein encoded by this gene affect the increase in blood glucose [14,15]. Gene polymorphisms are an important manifestation of genetic changes and genetic differences between people [16]. Previous studies have shown that gene polymorphisms of CAPN10 are correlated with type 2 diabetes mellitus in China, and the waist-hip ratio and body mass index of patients with the GG genotype of SNP43 were relatively high [17].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, rs7901695 polymorphism was independent of the risk for GDM in Poles and Brazilians [38,39]. Another meta-analysis showed that rs7903146 was strongly associated with the risk for GDM in Asian and Caucasian populations [40], but that rs7903146 polymorphism was not associated with GDM in either Germany or Poland [36,39]. Studies have also shown that the rs4506565 allele increased the risk of GDM in women in the United States and Denmark [10].…”
Section: Genes Involved In β-Cell Function and Insulin Secretionmentioning
confidence: 99%